Tourist itineraries for Sustainable Mobility: an application in the Salento Area (Italy) - Barbara Trincone (European Scientific Journal, ESJ, 2024)
The purpose of this work is to define the design process, implemented through an analytical methodology, of two sustainable mobility tourist routes in a specific area of southern Italy (Salento); methodology applicable to other territorial realities. This design process was developed in the context of the 2014/2020 Interreg V-A Greece-Italy cross-border cooperation strategic project called "AI SMART_Adriatic Ionian Small Port Network". It takes into account the analysis of existing Plans and Programs at different levels (Sustainable Mobility Urban Plans; cycling routes; Territorial Plans, etc.), the analysis of statistical data in the area related to employment and tourism; the interlocution with key stakeholders, the analysis of architectural, landscape and food and wine surpluses. These routes have been defined for the interaction of the port of Otranto with the hinterland territories and with the opposite Ionian coast to promote the sustainable and inclusive transnational tourist fruition of the Apulian territory. The genesis of the two thematic itineraries stems from the need/willingness to valorise some areas of Salento through the connection of significant nodes in terms of landscape, architectural and historical value, which define two routes with Pulsano and Otranto as their vertices. The project brings together the potential of the Salento as an area with a strong tourist value, with the theme of sustainable mobility, suggesting the seasonality of travel of each, to meet the needs of deseasonalization of an area with a high summer and seaside tourism vocation.